2021
DOI: 10.1161/jaha.120.019321
|View full text |Cite
|
Sign up to set email alerts
|

Women in Cardiology Twitter Network: An Analysis of a Global Professional Virtual Community From 2016 to 2019

Abstract: Background Social media is an effective channel for the advancement of women physicians; however, its use by women in cardiology has not been systematically studied. Our study seeks to characterize the current Women in Cardiology Twitter network. Methods and Results Six women‐specific cardiology Twitter hashtags were analyzed: #ACCWIC (American College of Cardiology Women in Cardiology), #AHAWIC (American Heart Association Women in Cardiology), #ilookli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…The use of "hashtag activism" has allowed WIC to connect through a common experience, but more importantly share that experience on a public platform through Twitter, elevating their voice and creating allies in the process. This social media activism has been used to promote a culture shift within the field of cardiology to create a more inclusive, respectful work environment 23 . Social media provides a unique opportunity to foster collaboration, networking, and mentorship, and dissemination of research which may help increase representation and help close the gender gap within the field 17,21 .…”
Section: The Rise Of Social Media and Hashtag Activismmentioning
confidence: 99%
See 3 more Smart Citations
“…The use of "hashtag activism" has allowed WIC to connect through a common experience, but more importantly share that experience on a public platform through Twitter, elevating their voice and creating allies in the process. This social media activism has been used to promote a culture shift within the field of cardiology to create a more inclusive, respectful work environment 23 . Social media provides a unique opportunity to foster collaboration, networking, and mentorship, and dissemination of research which may help increase representation and help close the gender gap within the field 17,21 .…”
Section: The Rise Of Social Media and Hashtag Activismmentioning
confidence: 99%
“…Analysis of the six key hashtag phrases identified showed that, over the period of three years (2016-2019), there was a 706% increase in tweets and retweets of tagged posts, a 207% increase in impressions, and a 440% increase in Twitter users, globally, sending tweets within the "Women in Cardiology Twitter Network" 23 . The momentous increase in Tweet shares and global impressions signifies the power of hashtags to reach a target audience.…”
Section: The Rise Of Social Media and Hashtag Activismmentioning
confidence: 99%
See 2 more Smart Citations
“…This network is highlighted by the consequential generation of >48,000 tweets, 266 million impressions and 12,485 users over a 3-year timeframe. 45 . Members often form real-life connections when they meet up at in-person cardiology conferences.…”
Section: ) Building a Wic Community Through Social Mediamentioning
confidence: 99%